Emotions and mood swings of pharmacy students in the context of the coronavirus disease of 2019 pandemic - Campos, Juliana Alvares Duarte Bonini [UNESP]; Campos, Lucas Arrais [UNESP]; Bueno, Julia Lucio [UNESP]; Martins, Bianca Gonzalez [UNESP] (Elsevier, 2021)
Introduction: The coronavirus disease of 2019 pandemic has changed university routines affecting student mental health. The aims of this study were to survey aspects related to mental health of pharmaceutical course students considering previous and current contexts. Methods: The Depression, Anxiety, and Stress Scale (DASS-21), Impact of Event Scale-Revised, and Brunel Mood Scale were used. DASS-21 was completed pre- and post-pandemic. The validity and reliability of the data were verified. The prevalence (95% CI) of mental health symptoms was estimated. The relationship between the time spent watching/reading the news and mean scales scores was evaluated (Pearson's correlation coefficient). Results: The prevalence of depression symptoms in students pre-pandemic was 66.7% (95% CI = 65.3–68.1) and during the pandemic was 81% (95% CI = 79.8–82.2). More than 70% (95% CI = 69.8–72.6) of participants had some psychological impact as a result of the pandemic (mild: 16.7% [95% CI = 15.6–17.8]; moderate: 9.1% [95% CI = 8.2–10]; severe: 45.4% [95% CI = 43.9–46.9]). High values of tension, depressed mood, mental confusion, and anger were observed. There was a significant correlation between the time spent following the news of the pandemic and symptoms of anxiety (r = 0.356; P <.001), stress (r = 0.248; P =.014), hyperarousal (r = 0.322; P ≤ 0.001), and intrusion (r = 0.21; P =.039). Conclusions: Students are highly vulnerable to depressive symptoms and mood swings due to the pandemic. These findings deserve consideration mainly from mental health professionals, but also from managers and educators.
Keywords: Anxiety; Depression; Mood; Pandemic; Psychological stress